Multipotent Stromal Cells Alleviate Inflammation, Neuropathology, and Symptoms Associated with Globoid Cell Leukodystrophy in the Twitcher Mouse1. (23rd August 2013) - Scruggs, Brittni A.; Zhang, Xiujuan; Bowles, Annie C.; Gold, Peter A.; Semon, Julie A.; Fisher‐Perkins, Jeanne M.; Zhang, Shijia; Bonvillain, Ryan W.; Myers, Leann; Li, Su Chen; Kalueff, Allan V.; Bunnell, Bruce A.
Abstract: Globoid cell leukodystrophy (GLD) is a common neurodegenerative lysosomal storage disorder caused by a deficiency in galactocerebrosidase (GALC), an enzyme that cleaves galactocerebroside during myelination. Bone marrow transplantation has shown promise when administered to late‐onset GLD patients. However, the side effects (e.g., graft vs. host disease), harsh conditioning regimens (e.g., myelosuppression), and variable therapeutic effects make this an unsuitable option for infantile GLD patients. We previously reported modest improvements in the twitcher mouse model of GLD after intracerebroventricular (ICV) injections of a low‐dose of multipotent stromal cells (MSCs). Goals of this study were to improve bone marrow‐derived MSC (BMSC) therapy for GLD by increasing the cell dosage and comparing cell type (e.g., transduced vs. native), treatment timing (e.g., single vs. weekly), and administration route (e.g., ICV vs. intraperitoneal [IP]). Neonatal twitcher mice received (a) 2 × 10 5 BMSCs by ICV injection, (b) 1 × 10 6 BMSCs by IP injection, (c) weekly IP injections of 1 × 10 6 BMSCs, or (d) 1 × 10 6 lentiviral‐transduced BMSCs overexpressing GALC (GALC‐BMSC) by IP injection. All treated mice lived longer than untreated mice. However, the mice receiving peripheral MSC therapy had improved motor function (e.g., hind limb strength and rearing ability), twitching symptoms, and weight compared to both the untreated and ICV‐treated mice. Inflammatory cell, globoid cell, and apoptotic cell levels in the sciatic nerves were significantly decreased as a result of the GALC‐BMSC or weekly IP injections. The results of this study indicate a promising future for peripheral MSC therapy as a noninvasive, adjunct therapy for patients affected with GLD. STEM Cells 2013;31:1523–1534